2018
DOI: 10.1073/pnas.1810067115
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in central executive network protects youth against cardiometabolic risks linked with neighborhood violence

Abstract: Although violent crime has declined in recent decades, it remains a recurring feature of daily life in some neighborhoods. Mounting evidence indicates that such violence has a long reach, which goes beyond family and friends of the victim and undermines the health of people in the surrounding community. However, like all forms of adversity, community violence elicits a heterogeneous response: Some remain healthy, but others deteriorate. Despite much scientific attention, the neural circuitries that contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…The association between more advanced pubertal staging and greater increases in internalizing severity during the pandemic was not significant in adolescents with above-average ECN coherence. Our findings are consistent with previous work showing that higher ECN connectivity protected youths against cardiometabolic risks associated with neighborhood violence ( 51 ) and was a marker of resilience to depression in adolescent girls with mothers who have a history of recurrent depression ( 52 ). In both of these studies, as well as in our own findings, connectivity of ECN regions differentiated resilient and susceptible adolescents with similar levels of risk for either physical or mental health difficulties.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The association between more advanced pubertal staging and greater increases in internalizing severity during the pandemic was not significant in adolescents with above-average ECN coherence. Our findings are consistent with previous work showing that higher ECN connectivity protected youths against cardiometabolic risks associated with neighborhood violence ( 51 ) and was a marker of resilience to depression in adolescent girls with mothers who have a history of recurrent depression ( 52 ). In both of these studies, as well as in our own findings, connectivity of ECN regions differentiated resilient and susceptible adolescents with similar levels of risk for either physical or mental health difficulties.…”
Section: Discussionsupporting
confidence: 92%
“…Together, our results demonstrate the specific role of the ECN in promoting resilience to maladaptive outcomes, as neither the DMN nor the SN exhibited effects consistent with a role in buffering against risk factors in any of these studies (including ours). Importantly, while ( 51 ) focused on an environmental risk factor and ( 52 ) focused on familial risk for depression, our study is the first to examine a biopsychosocial risk factor—off-time pubertal development—and the buffering role of the ECN against mental health difficulties during a period of major disruption and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 91 , 112 , 114 , 215 The overarching cognitive control network is therefore recruited to support control of belief and goal-directed strategies, flexibility creating a sense of self-agency that contributes to resiliency. 216 , 217 The dlPFC, which is a core node of the central executive network, is often activated during MM; MM enhances connectivity between the dlPFC and other executive-function regions. 218 , 219 As MM practice continues over time, the central executive network and other frontal networks may regulate the DMN in control of cognition.…”
Section: Mindful Self-regulationmentioning
confidence: 99%
“…These findings point to the importance of further research to understand causal dynamics, including longitudinal designs and multivariable models that include multiple aspects of neighborhood violence and other neighborhood characteristics, and which identify modifiable mediators or modifiers that might help mitigate the deleterious effects of neighborhood violence on mental health. For example, it has been found that community efficacy, defined as residents' willingness to intervene for the common good, partially mediates the association of neighborhood disadvantage and residential instability with violence (Sampson et al, 1997), and more recently that resting state connectivity within the central executive network moderates the impact of violence on cardiometabolic health (Miller et al, 2018). Conceivably, such information might lead to the development of interventions that help residents better cope with living in violent neighborhoods.…”
Section: Discussionmentioning
confidence: 99%